2020
DOI: 10.1111/1462-2920.14958
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophytes promote the accumulation of Amaryllidaceae alkaloids in Lycoris radiata

Abstract: Summary Lycoris radiata is a main source of Amaryllidaceae alkaloids; however, the low content of these alkaloids in planta remains a limit to their pharmaceutical development and utilization. The accumulation of secondary metabolites can be enhanced in plants inoculated with fungal endophytes. In this study, we analysed the diversity of culturable fungal endophytes in different organs of L. radiata. Then, by analysing the correlation between the detectable rate of each fungal species and the content of each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…In our study, a large proportion of OTUs from the seed surfaces was also detected in macerated seeds after surface sterilization. Endophytes can also enter the seed from the environment, and thus an overlap of surface and inner seed OTUs is expected to some extent (Shahzad et al 2018;Li et al 2019;Abdullaeva et al 2020;Ozkurt et al 2020;Zhou et al 2020;Patil and Maheshwari 2021;Santos and Olivares 2021). However, we cannot exclude the possibility that the macerated samples were contaminated with surface microbiota in our study, especially those of barley seeds, which have several outer layers that decrease the efficiency of sterilization.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, a large proportion of OTUs from the seed surfaces was also detected in macerated seeds after surface sterilization. Endophytes can also enter the seed from the environment, and thus an overlap of surface and inner seed OTUs is expected to some extent (Shahzad et al 2018;Li et al 2019;Abdullaeva et al 2020;Ozkurt et al 2020;Zhou et al 2020;Patil and Maheshwari 2021;Santos and Olivares 2021). However, we cannot exclude the possibility that the macerated samples were contaminated with surface microbiota in our study, especially those of barley seeds, which have several outer layers that decrease the efficiency of sterilization.…”
Section: Discussionmentioning
confidence: 89%
“…Carlton in absence of phytohormone, whereas high amounts of galantamine were detected in differentiated tissues cultured in low auxin (4 mg/L of NAA) as compared to undifferentiated tissue cultured in high auxin (20 mg/L of NAA) [54]. Furthermore, in nature it was observed that plants synthesize alkaloids in response to different biotic and abiotic factors [124]. Therefore, these factors, or the associated signaling compounds produced in response to these factors, can be used as elicitors to enhance the biosynthesis of specialized metabolites in in vitro techniques [125,126].…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 97%
“…The content of alkaloids assay was carried out by HPLC (Shimadzu, LC-20AT) on a reverse phase column (InertSustain C18, 5 µm, 4.6 mm × 250 mm) according to the method of Zhou et al [ 38 ]. The solvent composition was: phase A, 0.03% di-n-dibutylamine in H 2 O, phase B, acetonitrile.…”
Section: Methodsmentioning
confidence: 99%